Nilai Simbolis Tradisi Batu Qulhu Dan Fungsinya Dalam Pewarisan Sejarah Budaya Bagi Masyarakat Keturunan Melayu Di Desa Air Tenang, Aceh Tamiang - Desti Amanda Pratiwi (Jurnal Pengetahuan Sosial dan Sejarah, 2026)
This study discusses the symbolic values of the Batu Qulhu tradition and its function in the inheritance of cultural history among Malay descendants in Air Tenang Village, Aceh Tamiang. The Batu Qulhu tradition is a death ritual carried out on the 40th day after a person’s death by repeatedly reciting Surah Al-Ikhlas using white stones as a counting medium for dhikr. This study aims to identify the symbolic values contained in the Batu Qulhu tradition and its function in preserving and transmitting Malay cultural history. This research employed a qualitative method with an ethnographic approach. Data were collected through observation, interviews, and documentation. The results show that the Batu Qulhu tradition contains religious, social, cultural, and moral values that are still maintained by the Malay community in Air Tenang Village. The white stones used in the ritual symbolize purity, firmness of faith, and solemnity in worship. Furthermore, the Batu Qulhu tradition functions as a medium for transmitting cultural history because through this tradition, younger generations are able to recognize local customs, cultural values, and the identity of the Malay community inherited from previous generations. The tradition also strengthens social solidarity through collective prayers and communal cooperation.